Death Abroad – Legal Framework and Practices - Křepelka, Filip (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The paper addresses numerous practical aspects of death and dying abroad and related national, international and supranational legal framework. The role of international treaties and supranational law in the European Union without systematic controls of persons and goods on internal borders is highlighted. Death abroad is an event which causes increased challenge to the relatives of the deceased and the authorities of both host and home countries. Consular assistance is needed for certification of death and repatriation of remains. There is also intentional movement of persons for euthanasia and remains for funeral or for cremation abroad. Graves of soldiers and civilians which have died abroad during wars are protected with international standards. People prefer and reject various methods of disposal of remains and funeral rite. New methods emerge. Migration and globalization can thus result in controversies
Keywords: international and supranational law; death; funeral; crossborder movement; consular assistance; European Union